Specificity of tilt illusion reduction through perceptual learning - Jeong, Na-Ri; Han, Seungmin; Choi, Hoon (Frontiers in Psychology, 2024)
Human perceptual ability can be improved by perceptual learning through repeated exposure or training. Perceptual learning studies have focused on achieving accurate perception of stimuli by improving perceptual sensitivity. However, eliminating illusions can also be one of the ways of accurate perception. To determine whether the illusion can be attenuated by perceptual learning, the current study used a tilt illusion where the orientation of the grating presented in the center (central grating) was misperceived because of the orientation of the grating presented in the periphery (surrounding grating). In Experiment 1, participants were trained either in the illusion training condition, in which they trained with illusory stimuli presenting both surrounding and central gratings together, or in the control training condition, where only the central grating was presented. The results confirmed that the tilt illusion was reduced only in the illusion training condition. Experiment 2 tested the transfer effect of learning, which is not often observed in perceptual learning. During training, the orientation of the surrounding grating was fixed to see whether the elimination of the illusion also occurred in the surrounding grating with an orientation that was not used during training. A decrease in the illusion was found only in the case of a surrounding grating with trained orientations, and not in the case of surrounding gratings with untrained orientations. These results suggest that the reduction in tilt illusion through training is due to perceptual learning.